Al-Jughrāfiyyah wa-Tawẓīfuhā fī al-Aḥādīth al-Nabawiyyah (Dirāsah Taṭbīqiyyah) - Ramadhan, Ahmad Syahru (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This paper examines the application of geography in the Prophetic traditions (ḥadīth) and the attempt to identify an appropriate methodology for understanding ḥadīths related to geographical issues. The study employs a descriptive-analytical and inductive (istiqrāʾī) approach by collecting ḥadīths that hold significant relevance to geographical matters from both primary and secondary sources. The collected data are then analyzed with reference to works of ḥadīth commentary (sharḥ al-ḥadīth), fiqh literature, works on gharīb al-ḥadīth, and other supporting references. The findings of this research demonstrate an advantage over previous studies that have addressed similar topics. The study concludes that mastering geographical aspects in the interpretation of the Prophetic traditions yields several essential contributions: first, it enables a more accurate understanding of the ḥadīth; second, it contributes to uncovering the legal reasoning (‘illah) contained in the ḥadīth; and beyond that, geographical knowledge can serve as a tool to distinguish authentic ḥadīths truly attributed to the Prophet from those that are not.